THE EFFECTS OF DIFFERENT WARM-UP PROTOCOLS ON EXPLOSIVE LEG STRENGTH IN WOMEN SPORT GYMNASTICS - K. Herodek; M. Živković; E. Petković; S. Veličković; A. Aleksić-Veljković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The purpose of this study was to compare the acute effects of different protocols of warming-up using static, dynamic stretching and balet exercises on vertical jump performance. Ten girls in sport gymnastics completed three different protocols in randomized order. After each session, the athlets performed motorical test designed to measure explosive leg strength. Myotest was used for evaluating vertical jump performances and for data analyzing. For study research the statistical package "SPSS version 17" was used. To fortify the differences between three jump performances, the ANOVA and t-test were used.